Relationship between social media addiction, game addiction and family functions - Ebru Yayman; Okan Bilgin (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study examined the relationship between social media addiction, game addiction and family functions in adolescents. Respondent of this study is 762 students studying at four different high schools of the province of İstanbul. In the study, Pearson Moment Correlation Coefficient was found to determine the level of relationships between social media addiction, game addiction and family functions in adolescents. The effects of social media addiction and game addiction in adolescents on family functions were examined with regression analysis technique. When the relationships between social media addiction, game addiction and family functions in adolescents were examined, a positive relationship was found between social media and game addiction, while a positive significant relationship was found between both social media and game addiction and unhealthy family functions. In addition, it was also concluded that social media addiction and game addiction in adolescents were significant predictors of all subdimensions of family functions.